The Inducible Intein-Mediated Self-Cleaving Tag (IIST) System: A Novel Purification and Amidation System for Peptides and Proteins - A. Sesilja Aranko; Hideo Iwaï (Molecules, 2021)
An efficient self-cleavable purification tag could be a powerful tool for purifying recombinant proteins and peptides without additional proteolytic processes using specific proteases. Thus, the intein-mediated self-cleavage tag was developed and has been commercially available as the IMPACT™ system. However, uncontrolled cleavages of the purification tag by the inteins in the IMPACT™ system have been reported, thereby reducing final yields. Therefore, controlling the protein-splicing activity of inteins has become critical. Here we utilized conditional protein splicing by salt conditions. We developed the inducible intein-mediated self-cleaving tag (IIST) system based on salt-inducible protein splicing of the MCM2 intein from the extremely halophilic archaeon, Halorhabdus utahensis and applied it to small peptides. Moreover, we described a method for the amidation using the same IIST system and demonstrated 15N-labeling of the C-terminal amide group of a single domain antibody (VHH).